Answer:
84x^10
Step-by-step explanation:
The coefficients multiply, and the exponents add.
(4x)( -3x^6)(-7x^3) = (4)(-3)(-7)x^(1+6+3) = 84x^10
__
The rule for exponents is ...
(x^a)(x^b) = x^(a+b)
It's two. 50% chance of heads, 50% chance of tails.
The answer is 0.583, and the 3 has a bar notation
Hope this helped
btw i also do k12
Answer:
A) f^-1(x)=(x-8)^3+2
Step-by-step explanation:
To find the function inverse, switch the x with y and solve for y.
![y=\sqrt[3]{x-2}+8 \\\\x=\sqrt[3]{y-2}+8\\\\(x-8)^3 = y-2\\\\ (x-8)^3 + 2 = y](https://tex.z-dn.net/?f=y%3D%5Csqrt%5B3%5D%7Bx-2%7D%2B8%20%5C%5C%5C%5Cx%3D%5Csqrt%5B3%5D%7By-2%7D%2B8%5C%5C%5C%5C%28x-8%29%5E3%20%3D%20y-2%5C%5C%5C%5C%20%28x-8%29%5E3%20%2B%202%20%3D%20y)
Answer:
whats the question
Step-by-step explanation: